Protection of Traditional Health Knowledge: International Negotiations, National Priorities and Knowledge Commons. (January 2020) - Javed, Ghazala; Priya, Ritu; V. K., Deepa
Abstract: Traditional knowledge (TK) is under debate in the contemporary world for its inherent value and need for protection from 'biopiracy'. International consensus is proving difficult on defining its scope and ambit of protection. Traditional health knowledge (THK) is a promising domain of TK which, due to its immense economic and commercial value, is prone to misappropriation. International provisions exist for protection and definitions of TK and related resources at various fora such as the Convention on Biological Diversity. Proposals to protection of TK under Intellectual Property Right regimes are being addressed by the World Intellectual Property Organisation (WIPO). The text of a proposed treaty is being debated at WIPO's Intergovernmental Committee on Genetic Resources, Traditional Knowledge and Folklore (IGC-GRTKF). This article spells out the issues being negotiated at the WIPO-IGC-GRTKF. With THK characterised in a tiered manner based on its secret or diffused public availability, consideration of customary law is an imperative. India proposed that the national governments be given status of knowledge holders for THK in the public domain and fiduciary rights in case of closely held/associated THK. The article finds that a comprehensive national policy instrument and sui generis law for the protection of THK have become especially urgent in the light of international debates. It also proposes that, rather than Intellectual property (IP), the framework of a 'knowledge commons' for just sharing of TK and its innovations may be a better option.